Конституційні засади права на правову допомогу в Україні - Мартовицька, О. В.; Martovytska, O. V.; Олена Мартовицька (Юридична наука. - 2019. - № 9 (99). - С. 159-167, 2019)
Відзначено, що право на правову допомогу не тільки надається й реалізується на підставі й у відповідності до закріплених конституційних засад, а саме по собі виступає в якості одного з правових засобів, які використовуються для захисту прав і свобод людини. Аргументовано, що право на правову допомогу водночас є конституційним принципом, зокрема кримінального судочинства, який знаходить своє відображення в галузевому процесуальному законодавстві.

Everyone in Ukraine is born free and immediately acquires certain natural and private personal rights, such as the right to life, health, liberty, respect for his honor and dignity, the free development of his personality, and so on. The priority of every democratic state is not only to respect the constitutional rights and freedoms of the individual, but also to ensure the mechanism of their implementation. However, the average person, as a result of ignorance of their rights or ignorance of the mechanism of their implementation, often can not exercise them because they do not know how to act. In the article, it has been emphasized that the priority of every democratic state is not only to respect the constitutional rights and freedoms of the individual, but also to ensure the mechanism of their implementation. It has been noted that one of the effective means of exercising the rights and freedoms of the individual is the institution of legal aid, the general availability of which is due to the possibility of obtaining it free of charge for certain segments of the population. Emphasis has been placed on the fact that the right to legal aid is a constitutionally enshrined, and therefore guaranteed, right, which in itself is an integral principle of procedural activity in our state. At the same time, the granting and realization of this right also takes place on the basis of and in compliance with general principles. It has been emphasized that the right to a legal nature has a complex, multifaceted nature, according to which the studied law is both a constitutional principle that ensures equal access to justice and is exercised on the basis of other principles. It has been established that the right to legal aid is characterized by features that indicate its focus and nature. It has been noted that these features determine the constitutional principles of the right to legal aid – the focus on ensuring human rights and freedoms; legal nature; general character; impossibility of its restriction; state guarantee. It is has been noted that the right to legal aid is not only granted and exercised on the basis of and in accordance with the established constitutional principles, but in itself acts as one of the legal means used to protect human rights and freedoms. It has been argued that the right to legal aid is at the same time a constitutional principle, in particular criminal proceedings, which is reflected in the sectoral procedural legislation.

Отмечено, что право на правовую помощь не только предоставляется и реализуется на основании и в соответствии с закрепленными конституционными устоями, а само по себе выступает в качестве одного из правовых средств, используемых для защиты прав и свобод человека. Аргументировано, что право на правовую помощь является конституционным принципом, в частности уголовного судопроизводства, который находит свое отражение в отраслевом процессуальном законодательстве.
Constitutional principles of the right to legal aid in Ukraine
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; конституційні засади; constitutional principles; конституционные основы; право на правову допомогу; правова допомога; legal aid; правовая помощь; права та свободи громадян; rights and freedoms of citizens; права и свободы граждан; кримінальне судочинство; criminal justice; уголовное судопроизводство